Fostering Inclusive Adoption of RCM Through MDII Insights - Singaraju, Niyati; Gakhar, Shalini (International Rice Research Institute, 2025)
A study of rice farmers in India and Indonesia through the MDII framework revealed barriers and opportunities for the adoption and inclusiveness of agricultural digital tools like Rice Crop Manager, particularly for women and marginalized farmers. In today’s digital age, farmers adopt innovative tools to make more informed decisions in agrifood systems. One such application is the Rice Crop Manager (RCM), a web-based platform developed by the International Rice Research Institute (IRRI) and its partners. Launched in 2013, RCM offers field-specific crop and nutrient management recommendations, empowering farmers by helping boost yields and increase incomes. In the Philippines, using RCM led to an average yield increase of at least 0.4 tons per hectare per crop, providing an additional net benefit of USD 100 per cropping season. In India, this impact was even more significant, with farmers achieving a yield increase of 0.5 tons per hectare, equating to an added net benefit of USD 150 per hectare per season. While these numbers demonstrate the tool’s potential, a key question remains: are its benefits reaching everyone, especially women and marginalized farmers?